The Development of Critical Reading for German Learners through KWL Concept - Rina Evianty (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
German is taught as a foreign language in high schools or universities. Four basic language skills, namely listening, reading, speaking and writing are to be acquired. Listening and reading comprehension are receptive skills, while speaking and writing skills are productive skills. In reality, many german learners have difficulty reading. Teachers need to have proper reading strategies that can make it easier for german learners to understand text. Difficulties in reading comprehension or a general overstrain with the selected teaching texts can result in a lack of motivation to learn.  It could be that a technique used does not fit in the class. One strategy that can be used is the KWL (Know, Want to Know, Learned) reading strategy. The effect of this is that german learners become active themselves in the classroom and also show more motivation, as they can work together to develop titles, images and explanations of a text. The teacher is available to provide learners with information related to the topic. Then the topic is discussed together.  Then the learners write a few questions and try to determine them independently into information categories.  Finally they do a mapping and write a little résumé. They will also present their completed assignment while the teacher gives them comments. It has emerged from this that the use of technology in the class is more interested in reading lessons or also answer. They then discuss it with the others in order to awaken German learning.